AZD1222/ChAdOx1 nCoV-19 vaccination induces a polyfunctional spike protein-specific Th1 response with a diverse TCR repertoire. - Swanson, PA; Padilla, M; Hoyland, W; McGlinchey, K; Fields, PA; Bibi, S; Faust, SN; McDermott, AB; Snape, MD; Voysey, M; Lambe, T; Pollard, AJ; et al. (American Association for the Advancement of Science, 2021)
AZD1222 (ChAdOx1 nCoV-19), a replication-deficient simian adenovirus–vectored vaccine, has demonstrated safety, efficacy, and immunogenicity against coronavirus disease 2019 in clinical trials and real-world studies. We characterized CD4+ and CD8+ T cell responses induced by AZD1222 vaccination in peripheral blood mononuclear cells from 296 unique vaccine recipients aged 18 to 85 years who enrolled in the phase 2/3 COV002 trial. Total spike protein–specific CD4+ T cell helper type 1 (TH1) and CD8+ T cell responses were increased in AZD1222-vaccinated adults of all ages after two doses of AZD1222. CD4+ TH2 responses after AZD1222 vaccination were not detected. Furthermore, AZD1222-specific TH1 and CD8+ T cells both displayed a high degree of polyfunctionality in all adult age groups. T cell receptor β (TCRβ) sequences from vaccinated participants mapped against TCR sequences known to react to SARS-CoV-2 revealed substantial breadth and depth across the SARS-CoV-2 spike protein for both AZD1222-induced CD4+ and CD8+ T cell responses. Overall, AZD1222 vaccination induced a polyfunctional TH1-dominated T cell response, with broad CD4+ and CD8+ T cell coverage across the SARS-CoV-2 spike protein.